From language to creative writing : an introduction - Seargeant, Philip; Greenwell, Bill. (London : Bloomsbury Publishing Plc, 2013)
This textbook offers an innovative introduction to the study of the English language and the practices, skills and strategies of creative writing. For anyone studying English Language or Creative Writing at tertiary level or in higher education, or for developing writers and those interested in the nature of linguistic creativity, it offers a uniquely integrated approach. Readers will better understand the structure and uses of language and be able to use a full range of strategies in crafting and developing their own writing.Offering a detailed investigation of language, the authors examine both everyday use and examples from literature and the media to illustrate the diverse ways in which language is used in a variety of social contexts. They consider accent and dialect, standard and non-standard English, how language use varies according to its purpose, and the relationship it has to identity. Interwoven with the study of language are creative writing chapters that introduce strategies for the reader to draw upon in their own writing. Practical writing exercises develop the ability to select and shape language for different effects, create voice in a story, and utilise patterns of sound in the composition of poetry. This unique textbook will develop a better appreciation of language in use, as well as the skills to craft writing in distinctive ways.
Includes bibliographical references (pages 159-163) and index.
Keywords: English language -- Rhetoric; Creative writing